Perlindungan Hukum Terhadap Tenaga Kerja Wanita Ilegal di Malaysia - Muwahid, Muwahid; Syafa'at, Abdul Kholiq (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2018)
The research on legal protection of illegal female labors in Malaysia aims; knowing the implementation of legal protection against illegal female labors in Malaysia; knowing the factors that influence the implementation of legal protection against illegal female labors; and looking for solutions to optimize the implementation of legal protection against illegal female labors in Malaysia. The results of this study indicate that legal protection for illegal female labors in Malaysia is not optimally, because they lose their rights before the law, and are exacerbated by the majority working in the informal sector so that they are not reached by labor law. Of course this is not in accordance with the principle of the rule of law adopted by Indonesia, as contained in the 1945 Constitution of the Republic of Indonesia. The absence of a mechanism to protect illegal female workers is a state's neglect of the protection of human rights for all citizens, which is one of the main elements of the rule of law.